Microbes versus microbes: control of pathogens in the food chain. (30th May 2014) - Jordan, Kieran; Dalmasso, Marion; Zentek, Juergen; Mader, Anneluise; Bruggeman, Geert; Wallace, John; De Medici, Dario; Fiore, Alfonsina; Prukner‐Radovcic, Estella; Lukac, Maja; Axelsson, Lars; Holck, Askild; et al.
Abstract Foodborne illness continues as a considerable threat to public health. Despite improved hygiene management systems and increased regulation, pathogenic bacteria still contaminate food, causing sporadic cases of illness and disease outbreaks worldwide. For many centuries, microbial antagonism has been used in food processing to improve food safety. An understanding of the mode of action of this microbial antagonism has been gained in recent years and potential applications in food and feed safety are now being explored. This review focuses on the potential opportunities presented, and the limitations, of using microbial antagonism as a biocontrol mechanism to reduce contamination along the food chain; including animal feed as its first link. © 2014 Society of Chemical Industry